THE VIRTUAL CENSUS 2.0: A CONTINUED INVESTIGATION ON THE REPRESENTATIONS OF GENDER, RACE AND AGE IN VIDEOGAMES - Harrisson, Annie; Jones, Shawn; Marchessault, Jessie; Pedraça, Sâmia; Consalvo, Mia (AoIR Selected Papers of Internet Research, 2020)
While many studies suggest media representations of marginalized social groups play a vital role in shaping one’s worldview (Gerbner et al. 1994) or normalizing power imbalances (Harwood and Anderson 2002), videogames continue to privilege characters that are White, adult and male. This paper revisits key questions addressed in Williams, et al.’s “The Virtual Census: Representation of Gender, Race and Age in Videogames” (2009) to examine how representations of gender, race, and age in videogames have changed over the last ten years. The present study analyses the United Kingdom’s top 100 best-selling games of 2017 and looks for changing and continuing trends in the representation of videogame characters compared to the original study. While our sample still shows a preference for White, adult, and male characters, a small but significant increase in the representation of female characters and people of colour offers hope for the future of gaming. By revisiting the 2009 census, we aim to provide empirical evidence that may contribute to further discussions of how gender, race and age are portrayed in videogames, both within academic and industry circles.